Investigation of Pre-Service Science Teachers’ Social Media Usage Preferences: An Integrated Structural Equation Modelling and Artificial Neural Network Approach in the Context of Creativity and the Big Five Personality Traits - Doğru, M. Said; FATİH, YÜZBAŞIOĞLU (Sciendo, 2025)
Today, social media is widely used for many purposes, from socialization to communication and education to commerce. This study examines the social media use of pre-service science teachers in the context of creativity and the Big Five Personality Traits Theory. For this study, the participants were pre-service science teachers selected to represent the target group for examining the research objectives. Data from science teachers included in the study group were collected through an online questionnaire using purposive sampling, allowing for a focused examination of specific characteristics within this group. The data obtained from the questionnaires were analyzed and interpreted using an integrated SEM-ANN method. The findings obtained as a result of the study revealed that creativity and personality traits in the Big Five Personality Traits Theory affect the social media use of pre-service science teachers.
Keywords: Creativity; Neural Network Analysis; Science Teachers; Social Media; Structural Equation Modeling; Theory of the Big Five Personality Traits